Workshop on integrating biology instructional strategies with Al-Quran and As-Sunnah value for prospective biology teachers - Siti Robiah; E. Elfis; H. Hamzah; Afri Triyeni (Journal of Community Service and Empowerment, 2023)
The learning strategies carried out so far by biology teachers prioritize cognitive and psychomotor achievement targets so that affective aspects, especially the values of the Qur'an and As-Sunnah and the formation of Islamic character, tend to be neglected. As a result, it is necessary to provide prospective biology teachers with learning strategies that integrate the values of the Al-Qur'an and As-Sunnah in the hope that they can later be applied to their students. The learning strategies carried out so far by biology teachers prioritize cognitive and psychomotor achievement targets so that affective aspects, especially the values of the Qur'an and As-Sunnah and the formation of Islamic character, tend to be neglected. As a result, it is necessary to provide prospective biology teachers with learning strategies that integrate the values of the Al-Qur'an and As-Sunnah in the hope that they can later be applied to their students. The aim of this workshop is to equip Biology teacher candidates for Madrasah Aliyah and High School so that they have the knowledge and skills to apply Integrated Biology learning with the values ​​of the Al-Qur'an and As-Sunnah. The method of this activity is through a workshop which consists of several activities, namely Product Knowledge debriefing activities, discussion of the stages of the Al-Qur'an and As-Sunnah integrated learning model, simulations and assignments. The workshop was attended by 72 prospective teachers.. Based on the assignment to practice applying the 6 Phases of learning integrated with the values ​​of the Al-Qur'an and As-Sunnah, student skills are not very good. This could be due to several factors, including not being used to it.